Intellectual Data Analysis as a Component of Education Management - I. I. Ovsyanitskaya (Образование и наука)
The paper investigates the potential of the intelligent data processing tools presently implemented by economists, marketers and business analytics for solving the economic problems of synthesis and prognostication of financial processes based on quantitative and qualitative indicators.The adaptation of the above methods for pedagogical data processing and implementation in educational process can improve the education management quality and control. The paper presents the theoretical and practical aspects of the intelligent data analysis in pedagogy, the relevance of the problem being substantiated.The author looks at the origination and formation of the intelligent data analysis and gives the estimation examples of qualitative characteristics of teaching process, as well as the students’ personal characteristics based on the Data mining resources. The author recommends the ways for developing the patterns underlying the Data mining methods. The given approach in combination with the modern software tools can provide the data processing related to education management, i.e. pedagogical monitoring, identification of aspects affecting educational outcomes, early correction of educational department activities, etc.